Comparison of Immune and Systemic Inflammation Parameters in Patients with a Depressive Episode in Bipolar Disorder and Major Depressive Disorder: A Scoping Review - Anastasia A. Kasyanova; Polina A. Sobolevskaia; Oleg V. Limankin; Nataliia N. Petrova (Consortium Psychiatricum, 2024)
BACKGROUND: Many studies have aimed to investigate and compare immune system and systemic inflammation parameters in patients with bipolar disorder (BD) and major depressive disorder (MDD) suffering from a depressive episode. However, no systematic review of the results has been conducted so far.